A taxonomic revision of the Asian endemic subgenus Physocrema of the genus Crematogaster (Hymenoptera: Formicidae) - Hosoishi, Shingo; Ogata, Kazuo (Zootaxa, 2009)
The subgenus Physocrema of the genus Crematogaster is revised. Twelve species are recognized in the subgenus, of which two are new to science: C. (Physocrema) tanakai sp. nov. and C. (P.) yamanei sp. nov. An identification key based on the worker caste is provided. Taxonomic relationships between C. (P.) difformis and similar species are clarified. Crematogaster (P.) vacca Forel 1911 is raised to species level. The following new synonymies are proposed: C. (P.) inflata F. Smith 1857 = C. (P.) moorei Donisthorpe 1941 syn. nov.; C. (P.) mucronata Emery 1900 = C. (P.) fulmeki Forel 1922 syn. nov.; C. (P.) vacca Forel 1911 = C. (P.) stethogompha Wheeler 1919 syn. nov. = C. (P.) stethogompha detritinodis Wheeler 1919 syn. nov. Crematogaster (P.) onusta Stitz 1925 is referred to the subgenus Physocrema. C. tumidula Emery 1900 is transferred to the subgenus Oxygyne from Physocrema.